Global social policy in the making : the foundations of the social protection floor / Bob Deacon. - Deacon, Bob (Policy Press, 2013)
This book, by the world's leading authority on global social policy, examines why and how the Social Protection Floor became ILO, UN and G20 policy and how the World Bank and IMF took steps to lay its foundation.